The association between traffic-related air pollution and obstructive sleep apnea: A systematic review. (December 2020) - Clark, David P.Q.; Son, Dinh Bui; Bowatte, Gayan; Senaratna, Chamara V.; Lodge, Caroline; Perret, Jennifer L.; Hamilton, Garun S.; Dharmage, Shyamali
Summary: Recent evidence suggests that air pollution exposure may be a contributing risk factor for obstructive sleep apnea (OSA), however, current evidence is conflicting. This systematic review aims to determine the association between air pollution and OSA in the general population, and examine for potential effect modification by seasonality, temperature and humidity. Five full-text articles were included in the review out of 905 articles found by systematically searching PubMed, Embase and Scopus databases. The included studies were limited to OSA in adults that were conducted in middle to high-income countries. The results highlight heterogeneity in the diagnostic criteria for OSA and method used to assess air pollution exposure. There is some evidence to support a relationship between air pollution exposure and OSA. However, the duration of exposure to different air pollutants including particulate matter (PM2.5 and PM10 ) and nitric oxides (NO2 ) in relation to OSA varied across different seasons, temperatures, and countries. This variability of the pollutants across studies warrants a more robust study design using time-series analysis with multiple follow-ups to strengthen the evidence for this relationship before considering its implications.